Tenure Choice, Portfolio Structure and Long-Term Care - Optimal Risk Management in Retirement - Hans Fehr; Maurice Hofmann (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the interplay between tenure decisions, stock market investment and the public social security system. Housing equity not only serves a dual purpose as a consumption good and as an asset, but also provides insurance to buffer various risks in retirement. Our life cycle model captures these links in order to explain why homeownership in Germany is so low. Our simulation results indicate that the public long-term care as well as the pension system reduce the homeownership rate in Germany by 10-15 percentage points.
Keywords: C61; D15; G11; H55; 330; homeownership; stock market participation; life-cycle models; long-term care